Bentuk-bentuk Pelanggaran terhadap Tata Tertib Sekolah oleh Peserta Didik di SMA dan Implikasinya bagi Layanan Bimbingan dan Konseling - Anwar, Elvina; Sano, Afrizal (Lembaga Yasin AlSys, 2024)
This research is motivated by the number of students who violate school rules. This study aims to describe the form of students' violations of school rules related to: (1) attending ceremonies, (2) clothing and makeup, (3) laboratory use, (4) doing homework, (5) paying tuition fees, (6) the learning process, (7) absence and leaving school, 8) worship. The research method used is a quantitative method with a descriptive approach. The sample in this study were 77 students of SMA N 8 Padang using purposive sampling technique. For data processing using descriptive statistical methods. The results showed that the forms of violation of the rules by students were (1) 46% of students often did not use school attributes during the flag ceremony, (2) 58.4% of students often did not use complete school attributes, (3) 32.4% of students rarely used laboratory coats and complete personal protective equipment, (4) 19, 4% of students rarely do every assignment given independently without cheating friends, (5) 32.4% of students often deliberately do not pay school fees, (6) 48% of students often go to the canteen when there is no teacher in class, (7) 50.2% of students often ask permission from teachers via whatsapp and students are often late entering the classroom after recess, (8) 24.6% of students rarely perform 5-time prayers.